2001
DOI: 10.1021/ol000386i
|View full text |Cite
|
Sign up to set email alerts
|

Photoallylation and Photoreduction of Cyclohexylidenepropanedinitrile by Use of Allyltrimethylsilane via Photoinduced Electron Transfer:  Control of the Product Ratio Depending on pKa Values of Additives

Abstract: Irradiation of an acetonitrile solution containing cyclohexylidenepropanedinitrile (1) and allyltrimethylsilane (2) in the presence of phenanthrene afforded two kinds of allylated products (3, 4) and a reduction product (5). The product ratio of 3, 4, and 5 dramatically changed depending on the pK(a) values of additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
(13 reference statements)
0
15
1
Order By: Relevance
“…The product ratio of allylation and reduction (3/4) listed inTable 1are lower than the previous report using cyclohexylidenepropanedinitriles[10,16]. The difference in the product ratio between previous and current studies may be due to the increased steric hindrance to protonation, and also due to the decrease of stoichiometry of carboxylic acids added in order to increase de.…”
contrasting
confidence: 65%
See 2 more Smart Citations
“…The product ratio of allylation and reduction (3/4) listed inTable 1are lower than the previous report using cyclohexylidenepropanedinitriles[10,16]. The difference in the product ratio between previous and current studies may be due to the increased steric hindrance to protonation, and also due to the decrease of stoichiometry of carboxylic acids added in order to increase de.…”
contrasting
confidence: 65%
“…The formation of 4 was explained by hydrogen abstraction of 5, or an electron transfer from 1 -• to 5 followed by protonation, or disproportionation of 5 to give 1 and 4. We have previously reported pK a -dependency of the photoallylation and photoreduction of cyclohexylidenepropanedinitriles with 2 [10]. In the presence of a relatively strong acid such as carboxylic acids, radical anion is protonated at their b-positions, and the ratios of pathways of hydrogen abstraction from b-position of the radical anion followed by protonation at a-position and hydride transfer from the radical anion increase with decreasing acidity of the additives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each photoreaction described above takes place through a process termed photoredox sensitization by phenanthrene (Phen) (Scheme 4) [22,23,24,25,26,27]. In the pathway, the excited singlet state of Phen, generated by light absorption, transfers one electron (SET (single electron transfer)) to the electron-deficient alkene 1 to form the phenanthrene radical cation (Phen •+ ) and the alkene radical anion 1 •− .…”
Section: Resultsmentioning
confidence: 99%
“…Because radical ions that serve as intermediates in these processes are short-lived and highly reactive, control of the stereochemistry of these reactions is often difficult [15,16,17,18,19,20,21]. We have previously developed photoallylation and photoreduction reactions of electron deficient alkenes with allyltrimethylsilane that occur via PET pathways [22,23,24]. In addition, we also demonstrated that diastereoselectivity of this process can be achieved by steric control of allyl radical or proton addition to radical anions that are generated from electron deficient alkenes (Scheme 1) [25,26,27].…”
Section: Introductionmentioning
confidence: 99%